The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0104-66321998000200010
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Methane Steam Reforming in a Membrane Reactor: An Isothermic Model

Abstract: A mathematical modelling of one-dimensional, stationary and isothermic membrane reactor for methane steam reforming was developed to compare the maximum yield for methane conversion in this reactor with that in a conventional fixed-bed reactor. Fick's first law was used to describe the mechanism of hydrogen permeation. The variables studied include: reaction temperature, hydrogen feed flow rate and membrane thickness. The results show that the membrane reactor presents a higher methane conversion yield than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The use of hydrogen as a clean energy vector is every day more recurrent: combustion of hydrogen results in water and, particularly, its environmental impact is very limited when produced from renewables [3][4][5]. Currently, the principal source of hydrogen is the reforming of hydrocarbons, mainly methane [6]. As a result of the methane steam reforming some compounds like CO, CO2, H2O, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hydrogen as a clean energy vector is every day more recurrent: combustion of hydrogen results in water and, particularly, its environmental impact is very limited when produced from renewables [3][4][5]. Currently, the principal source of hydrogen is the reforming of hydrocarbons, mainly methane [6]. As a result of the methane steam reforming some compounds like CO, CO2, H2O, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane microreactors are an important class of microreactors that combine reaction and separation in one single device. Thus, for example, a thin palladium membrane can be included which separates hydrogen from the reformate gas mixture (Alfadhel and Kothare, 2005;Assaf et al, 1998;Karnik et al, 2003). Assaf et al (1998) modeled the methane steam reforming in an isothermal membrane reactor and concluded that the membrane reactor, besides providing purified hydrogen still presents a higher methane conversion yield than the conventional fixed-bed reactor.…”
Section: Microreactorsmentioning
confidence: 99%
“…Thus, for example, a thin palladium membrane can be included which separates hydrogen from the reformate gas mixture (Alfadhel and Kothare, 2005;Assaf et al, 1998;Karnik et al, 2003). Assaf et al (1998) modeled the methane steam reforming in an isothermal membrane reactor and concluded that the membrane reactor, besides providing purified hydrogen still presents a higher methane conversion yield than the conventional fixed-bed reactor. This work presents a two-dimensional mathematical model of an isothermal membrane microreactor operating under steady-state conditions for use as a source of pure hydrogen for a PEM fuel cell from ethanol steam reforming catalyzed by Ni/Al 2 O 3 .…”
Section: Microreactorsmentioning
confidence: 99%
“…The development of oxygen permeable membranes has opened up a new possibility to enhance the partial oxidation of methane process. New improvements are been done in membrane materials and structures, which supports the selective compound in porous alumina, porous ceramic substrate, and in nanostructured carbides, and several works suggests the oxygen-permeating dense membranes have potential applications in partial oxidation of methane (Balachandran et al, 1997;Tsai et al, 1997;Kao et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The modeling and simulation of catalytic membrane reactors for methane conversion to syngas has been done by some authors, specially on steam reforming of methane and oxidative coupling of methane (Shu et al, 1994;Wang and Lin, 1995;Kao et al, 1997;Assaf et al, 1998;Chen et al, 2003;Lin et al, 2003;Gallucci et al, 2004). Very few works have dealt with partial oxidation of methane in membrane reactors (Tsai et al, 1997;Jin et al, 2000) and none dealing with the production of syngas for gas-to-liquid (GTL) processes.…”
Section: Introductionmentioning
confidence: 99%